The Web Warrior Guide to Web Programming - Xue Bai (Thomson course Technology, 2003)
Finally, a complete Web programming survey book! This overview of the most current programming languages and tools used to develop dynamic, data-driven, interactive, applications is perfect for the beginning programmer